Brighter than before : a novel - Walsh, Courtney, 1975- (Thomas Nelson, 2026)
"After a painfully public discovery shatters her marriage, along with her picture-perfect, country club life, Claire finds herself suddenly single and faced with a blank page for a future. On that page she writes a simple list that reads like equal parts dare and daydream -- Move to a new city. Make a real friend. Get a job I love -- and she vows to accomplish every single one. Before she can talk herself out of it, she takes a step of faith, puts her old life in the rearview mirror, and leases an apartment in Chicago, the city that has always had her heart. This one step sends Claire on a journey of self-discovery, giving her the courage to conquer her fears, one checklist item at a time, and showing her that life can be a whole lot brighter than she imagined. She rediscovers a love for baking, stumbles into new friendships, and even allows her daughter, Minnie, to create a dating profile and choose her dates for her. Perhaps the biggest surprise, though, is Miles, the charming, off-limits neighbor whose kindness makes it hard to remember why he's off-limits at all. Between late-night journaling, disastrous first dates, great big lessons and priceless small victories, Claire learns to quiet the voice telling her she wasn't enough and listens to the one that asks the harder question ... What do I really want? As old expectations loosen their grip, Claire discovers that belonging isn't a place you're invited to -- it's a life you build one brave choice at a time. And the sweetest things often show up when you finally get out of your own way." --